Mechanical characteristics and permeability evolution rule of coal under loading-unloading conditions - ZHAO Hong-gang; ZHANG Dong-ming; LIU Chao; DENG Bo-zhi; BIAN Guang; LI Wen-pu (工程科学学报, 2016)
Based on the self-made servo-controlled seepage equipment for thermal-hydrological-mechanical coupling of coal and rock, a loading and unloading experimental study was performed by increasing the axial compression and decreasing the confining pressure in consideration of the actual mining method. The mechanical characteristics and permeability evolution rule of coal were analyzed and studied under loading-unloading conditions. The results show that during the process of loading and unloading, the faster the loading rate of axial stress, the longer the platform of the stress-strain curve near the peak, and the larger the peak stress, axial strain and circumferential strain, while the smaller the volume strain. The deformation moduli at different loading and unloading rates exhibit the trend of rapidly decreasing first and then slowly decreasing. When damage occurs, the deformation modulus rapidly decreased and then is nearly constant. Under that condition of the same axial strain, the deformation modulus increases with the decrease of loading and unloading rate. The relations of deviatoric stress and coal permeability with strain can be divided into three stages in the whole test process:initial compaction and elastic stage, yield stage, and post-failure stage. During the process of loading and unloading, the slower the loading and unloading rate is, the larger the coal permeability and volume strain become when the axial stress of coal samples reaches the peak value.